2018
DOI: 10.1007/s12350-017-0901-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a clinical pathway to assess asymptomatic renal transplant candidates using myocardial perfusion imaging

Abstract: Asymptomatic kidney transplant candidates with ≥3 AHA/ACCF risk factors are at increased cardiac risk, and should be considered for noninvasive CAD surveillance. Intermediate risk patients (3-4 factors) benefit the most from pre-transplant MPI to define long-term MACE risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…The study also confirmed that the presence of 3 or more of these risk factors is an effective threshold to use in order to derive a significant incremental predictive value from stress MPI in this population. (14)…”
Section: Cardiovascular Risk Stratification For Esrd Patientsmentioning
confidence: 99%
“…The study also confirmed that the presence of 3 or more of these risk factors is an effective threshold to use in order to derive a significant incremental predictive value from stress MPI in this population. (14)…”
Section: Cardiovascular Risk Stratification For Esrd Patientsmentioning
confidence: 99%
“…In 2012, the American Heart Association and the American College of Cardiology Foundation (AHA/ACCF) published a scientific statement regarding cardiac evaluation in kidney and liver transplantation candidates. The statement indicates that “noninvasive stress testing may be considered in liver transplantation candidates with no active cardiac conditions on the basis of the presence of multiple CAD risk factors regardless of functional status.” [8, 9] These risk factors include age > 60 years, prior cardiovascular disease, hypertension, dyslipidemia, diabetes mellitus, smoking, and left ventricular hypertrophy [8]. The burden of these risk factors that should prompt non-invasive stress testing in asymptomatic patients has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Standardization of medical treatment with implementation of clinical pathways is taking place in many health domains . In urology, the clinical pathways only regard cancer treatment and have all optimized the care of patients .…”
Section: Introductionmentioning
confidence: 99%